A Case study on Mountain Haven development Inc.'s executive committee decision-making process - Celo, Gold Ann Marie P.
This study was conducted in order to analyze the decision-making process of the executive committee of Mountain haven development Inc., a Real Estate Dealer & subdivision Operator. It incorporated the different concepts of Speech Acts, Bales and Strodbeck's Phasic Regression and Conversation Analysis approach in examining the decision-making process of the executive committee. Inverting the perspective that communication in a form of discussion is a tool decision-makers use to go about the process of decision making, this study proposed a fresh insight that discussion in meetings provide the avenue for the participants to create, select, modify, and derive decisions, that the process unfolds in a dynamic of four distinct types of conversation. Basically, it assumed that first, decision-making is a complex and recurring activity through which they produce in meetings. The process of the decision-making, how it moves around the four types conversation, the factors that motivates progression, and the importance of utterances were also given in the study.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication